Managing financial market expectations: The role of central bank transparency and central bank communication - Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
In this paper, we study the influence of central bank transparency and informal central bank communication on the money market adjustment process between two interest rate decisions. The sample covers nine major central banks for the period from January 1999 to July 2007. We find, first, that both transparency and communication facilitate understanding upcoming interest rate decisions. Second, transparency, as measured by various subcategories of the Eijffinger and Geraats (2006) index, leads to better anticipation of monetary policy. Provision of information on (unanticipated) macroeconomic disturbances and explicit prioritization of central bank objectives are the most important of these subcategories. Finally, there is no unique optimal design for central banks as (i) a very high degree of transparency, (ii) frequent communication on an informal basis, (iii) gradualism in target rate changes, or (iv) a high frequency of interest rate decisions all contribute to sound understanding regarding future interest rate decisions.
Keywords: E52; E58; 330; central bank communication; central bank transparency; financial market expectations; interest rate decision; monetary policy; money market; Geldpolitik; Zinspolitik; Staatliche Information; Ankündigungseffekt; Zins; Erwartungstheorie; Geldmarkt; Schätzung; Industriestaaten